Primary School Policies and Practices: A Systematic Literature Review as a Basis for Evidence-Based Policy Recommendations - Rahman, Annisa Rifah; Rezkilaturahmi, Rezkilaturahmi; Rahman, Hardianto; Razali, Nur Zalikha Binti (Lia Center of Research and Education, 2025)
This study aims to analyze trends and empirical findings on primary school policies and practices in Indonesia and internationally. The study uses a qualitative design through a Systematic Literature Review approach. A total of 884 articles were identified using Publish or Perish software, then selected using the PRISMA protocol, resulting in 34 articles that met the criteria for in-depth analysis. The data were analyzed using a thematic analysis framework to identify key themes and research gaps. The results showed that 60% of the empirical studies reviewed highlighted policy aspects, while the other 40% focused on practices in primary schools. The analysis stated that the effectiveness of education policy is highly dependent on school leadership, management transparency, and the availability of adequate infrastructure. Innovative practices such as character education, literacy development, and transdisciplinary learning have been shown to contribute positively to improving the quality of elementary schools. This study provides recommendations in the form of 6 months of continuous training at the beginning of leadership for school principals and a collaboration forum for public and private elementary school teachers as a regular discussion forum for good practices with incentives in the form of accreditation points and 21st-century learning innovation grant funds for schools that actively participate.